The role of product innovation on the diffusion of mobile telephony - Heli Koski; Tobias Kretschmer (The Research Institute of the Finnish Economy (ETLA), 2009)
Most existing empirical work on technology diffusion assumes technologies to remain constant throughout the diffusion process. However, many consumer technologies improve significantly over time. Using data on the characteristics of new mobile handsets over a ten-year period and controlling for potential endogeneity problems, we find that handset quality and variety had a significant impact on the global diffusion of mobile telephony. Our estimation results further suggest that earlier empirical studies on diffusion may have attributed too much of diffusion to network effects.
Keywords: L96; O33; 330; Product innovation; Technology Diffusion; Mobile Telephony; Innovation; Technischer Fortschritt; Innovationsdiffusion; Mobiltelefon; Welt